ExSIDE: Component Based Object Oriented Expert System’s Integrated Development Environment - Mohamad Hanif Md Saad; Rabiah Adawiyah Shahad; Kong Win; Aini Hussain (JOIV : International Journal on Informatics Visualization, 2017)
This paper describes the design and development of a component-based object oriented Expert System's Integrated Development Environment (ExSIDE).  It is integrated with (i) a user-friendly manual and automated knowledge acquisition and management tool (ExSIDE_KAMT);(ii) an independent and customizable runtime module (ExSIDE_RTM); (iii) an object-oriented in-process Component Object Model (COM)-based inference engine (ExSIDE_IE); (iv) an object-oriented out-of-process COM-based inference engine (ExSIDE_IESvr); (v) and a PHP based inference engine (ExSIDE_PHP). ExSIDE_RTM can function independently as an Expert System Shell (ESS) and helps user to develop Expert Systems rapidly.  ExSIDE_IE and ExSIDE_IES can be integrated with COM-supporting general purpose and scientific application development tools such as variants of C/C++/C#, BASIC (Visual BASIC®, REALbasic®), Java, MATLAB®, LabVIEW®, and Mathematica® to develop more advanced Expert Systems. Finally, ExSIDE_IE and ExSIDE_PHP can be used with Active Server Pages (ASP) and PHP technologies to generate web based Expert Systems. The unique framework of the ExSIDE enables rapid development of Expert Systems' on PC and web for technical and non-technical users. The overall system was developed successfully, and its usability was demonstrated via five unique Expert Systems case studies discussed in this paper.